Influence of nickel dopent on the supercapacitor and magnetic properties of nanostructured manganese dioxide. (6th December 2022) - Ashokkumar, K; Dhanapandian, S; Suthakaran, S; Krishnakumar, N
ABSTRACT: Nickel-doped manganese dioxide nanoparticles (Ni = 0.025, 0.05, 0.075, 0.1 and 0.125 M) were prepared via a facile hydrothermal method. Their structural properties, surface morphology, functional groups and magnetic properties were studied by different techniques like X-ray diffraction, Scanning Electron Microscopy and vibrational spectroscopy. The XRD results revealed that the position of diffraction peaks agreed well with the reflection of a tetragonal structure. The crystallite size ranged from 9.2 to 27.61 nm. SEM images exhibited a smooth surface rod-shaped structure. FTIR studies showed slight shifting of the Mn-O band, which ensured the growth of nanorods. The cyclic voltammetry measurements of Ni-doped MnO2 nanoparticles exhibited an excellent capacitance performance than pure MnO2 . At room temperature, the MnO2 nanoparticles exhibited paramagnetic behaviour, whereas Ni-doped MnO2 nanoparticles exhibited superparamagnetic behaviour. This work provides a pathway for the development of high-performance supercapacitors as well as the improvement of magnetic properties of the MnO2 nanomaterials.